2018
DOI: 10.3126/jgmcn.v10i2.20804
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Adverse Drug reactions: A Four-Year Study from Western Nepal

Abstract: Background: Cutaneous adverse drug reactions (CADRs) range from minor reactions to several life threatening complications. Objectives: To study the clinical spectrum of cutaneous adverse drug reactions, determine the causative drugs responsible for the reactions and to assess the preventability.Methods: The study was carried out in the Department of Dermatology of Gandaki Medical College Teaching Hospital from June 2011 to June 2015. All the patients attending the Dermatology Outpatient Department and the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Karbamazepin merupakan golongan anti-konvulsan yang biasa dipakai pada penyakit-penyakit seperti epilepsi, neuralgia trigeminal, neuralgia diabetes mellitus, neuralgia glosofaringeal, dan neuralgia post herpetik. 4 Pada penelitian ini, seluruh pasien kami mendapatkan karbamazepin untuk gangguan psikosomatis.…”
Section: Pendahuluanunclassified
“…Karbamazepin merupakan golongan anti-konvulsan yang biasa dipakai pada penyakit-penyakit seperti epilepsi, neuralgia trigeminal, neuralgia diabetes mellitus, neuralgia glosofaringeal, dan neuralgia post herpetik. 4 Pada penelitian ini, seluruh pasien kami mendapatkan karbamazepin untuk gangguan psikosomatis.…”
Section: Pendahuluanunclassified
“…Research conducted by Jha N et al showed similar results with cephalosporins at 22.73% and carbapenems at 17.27% [3]. Several cephalosporin drugs were found to trigger cutaneous adverse drug reactions, including ceftriaxone, cefixime, and cefotaxime [14,16,17].…”
Section: Administrationmentioning
confidence: 86%
“…Cutaneous adverse drug reactions are usually caused by antibiotics, non-steroidal anti-inflammatory drugs (NSAIDs), and anticonvulsants [3,5,11]. The cause that is often found as a trigger for the exanthematous drug eruption is antibiotics [13,14,15]. Classes of antibiotics that often cause this condition are β-lactam such as penicillins, cephalosporins, and carbapenems [3,13,15].…”
Section: Administrationmentioning
confidence: 99%
“…The second common CADR was seen is Fixed drug eruption (FDE) with about (13.3%) followed by Erythematous rash that showed (11.1%), Toxic Epidermal Necrolysis (TEN) and Urticaria recording (7.5%).in which 1 was fatal with TEN wherein similar mortality with TEN was seen in the study of Saraswoti neupane and Surya Raj Sharma (2012) 12 Steven Johnson Syndrome (SJS) were identified in (4.4% 23 The results of assessment of the severity index revealed most cases with Moderate about (62.2%), followed by Mild about (26.6%). (10%) were identified as Severe .One case (1.1%) was fatal which was similarly seen in the study by Saraswoti neupane and Surya Raj Sharma (2012) 12 In our study all the cases were Type B (Bizarre type) which was similarly seen in the study by Karamsad Suthar J. and Desai S.V (2011) 19 where 100% ACDRs were Type B (Bizarre immunological allergic drug reaction).…”
mentioning
confidence: 82%